2018
DOI: 10.22159/ijpps.2018v10i3.24372
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative, Anti-Inflammatory and Anti-Atherosclerotic Effect of Taurine on Hypercholesterolemia Induced Atherosclerotic Rats

Abstract: Objective: The present study evaluates the antioxidant, anti-inflammatory and anti-atherosclerotic potency of taurine (2-amino ethane sulfonic acid) when administered orally to hypercholesterolemia induced atherosclerotic rats.Methods: The experimental atherosclerosis was induced by feeding rats with an atherogenic diet comprising of the normal rat chow supplemented with 4 % cholesterol, 1 % cholic acid and 0.5 % thiouracil (CCT diet) for 20 d. Treatment with atorvastatin (10 mg/kg body weight) and taurine (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(20 reference statements)
1
6
0
1
Order By: Relevance
“…Quantifying this MDA will positively reflect the severity of an ongoing oxidative damage treatment with fruit rind extract of G. gummi-gutta significantly reduced the TBARS level in a dose-dependent manner. The increase in the MDA which is indicative of ongoing oxidative damage was due to oxidative stress induced by HLD [27]. In our study, a significant reduction in TBARS values was observed following treatment with the extract, wherein the maximum reduction was evident with a higher dose of the extract.…”
Section: Discussionsupporting
confidence: 54%
“…Quantifying this MDA will positively reflect the severity of an ongoing oxidative damage treatment with fruit rind extract of G. gummi-gutta significantly reduced the TBARS level in a dose-dependent manner. The increase in the MDA which is indicative of ongoing oxidative damage was due to oxidative stress induced by HLD [27]. In our study, a significant reduction in TBARS values was observed following treatment with the extract, wherein the maximum reduction was evident with a higher dose of the extract.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, taurine is abundant in marine organisms, and it can be extracted from the offal of marine product processing to improve the utilization of marine resources and reduce environmental pollution . Dietary taurine could protect against the development of cardiovascular diseases caused by high fat or high cholesterol via decreasing the hepatic cholesterol ester secretion. Oral supplementation of 2% taurine inhibited atherosclerotic lesions by decreasing the serum tumor necrosis factor α (TNF-α) and interleukin 1α (IL-1α) levels in hypercholesterolemic rats . However, the effects and involving mechanism of TMAO and high fat/high cholesterol on atherosclerosis were different .…”
Section: Introductionmentioning
confidence: 99%
“…14−16 Oral supplementation of 2% taurine inhibited atherosclerotic lesions by decreasing the serum tumor necrosis factor α (TNF-α) and interleukin 1α (IL-1α) levels in hypercholesterolemic rats. 17 However, the effects and involving mechanism of TMAO and high fat/high cholesterol on atherosclerosis were different. 18 Marine foods rich in high TMAO also contain high levels of taurine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a study conducted by Sharma et al, antioxidative, anti-inflammatory, and antiatherosclerotic effect of taurine on hypercholesterolemia induced atherosclerotic rats was evaluated. Oral administration of taurine to rats showed antioxidant and anti-inflammatory activity by modulating oxidants in favor of reducing oxidative stress and also showed antiatherosclerotic activity in hypercholesterolemia-induced atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%